Geoelectrical Method for Detecting the Limit of Liquid Waste Flowing Below the Surface at Piyungan Landfill. Issue 1 (January 2021) - Jayadi, H; Muin, M R; Sabhan,; Meidji, I U
Abstract: Increasingly limited residential land in urban areas results in residents looking for and making settlements around landfills. This affects people's lives in fulfilling their daily needs, clean water. To meet the demand for clean water, some residents use well water as the primary drinking water source. Judging from the condition of the residential areas located in the landfill area, there may be an effect of waste, especially liquid waste, on well water sources. For this reason, research is carried out using the geoelectric method by combining two configurations, namely Schlumberger and dipole-dipole. So that it can provide an overview of the boundaries of liquid waste contaminants in the soil, which are associated with conductive fluids that affect the quality of clean water from residential areas around the landfill. In this study, it was found that the fluid flow associated with liquid waste has a lateral movement to the right with a depth of 24.5 meters.